After the end of history : American fiction in the 1990s - Cohen, Samuel S. (University of Iowa Press, 2009)
In this bold book, Samuel Cohen asserts the literary and historical importance of the period between the fall of the Berlin wall and that of the Twin Towers in New York. With refreshing clarity, he examines six 1990s novels and two post-9/11 novels that explore the impact of the end of the Cold War: Pynchon's Mason & Dixon, Roth's American Pastoral, Morrison's Paradise, O'Brien's In the Lake of the Woods, Didion's The Last Thing He Wanted, Eugenides's Middlesex, Lethem's Fortress of Solitude, and DeLillo's Underworld. Cohen emphasizes how these works reconnect the past to a present that is iro.